Reliability and validity of the maximal anaerobic running test - Nummela, A.; Alberts, M.; Rijntjes, R. P.; Luhtanen, P.; Rusko, H. (International Journal of Sports Medicine, 1996)
Physically active men (n = 13) twice performed the Maximal Anaerobic Running Test (MART) on a treadmill and once the Wingate Anaerobic Test (WAnT) on a cycle ergometer. The MART consisted of n 20-s runs with 100-s recovery between the runs. The speed of the first run was 14.6 km.h-1 and the inclination 4 degrees. Thereafter, the speed was increased by 1.37 km.h-1 every run until exhaustion. During all tests oxygen uptake was measured breath-by-breath and blood samples were taken from the fingertip 40s after each run to determine the lactate concentration (BLa). Power at submaximal BLa levels and maximal power (P5mM, P10mM and Pmax, respectively) were calculated and P was expressed as the oxygen demand of running according to the American College of Sports Medicine equation. In the MART the Pmax was 108 ml.kg-1.min-1 and peak BLa was 15.6 mM. The reliability for the power indices in the MART were as follows: r = 0.92 (p < 0.001) for Pmax r = 0.80 (p < 0.001) for P10mM and r = 0.67 (p = 0.01) for P5mM. The average contribution of anaerobic energy expenditure was calculated to be 68% but it ranged from 64% to 72% during the MART. Although four out of seven of the correlations between the corresponding variables of the MART and WAnT were significant (0.52 < r < 0.59) they were not high. It is concluded that the anaerobic energy production is high in the MART, the test is reliable, and that the treadmill and cycle ergometer test measure slightly different qualities.